Investigation Into The Causes Of Delays And Cost Overruns In Uganda's Public Sector Construction Projects - Alinaitwe, Henry; Apolot, Ruth; Tindiwensi, Dan (Penerbit Universiti Sains Malaysia, 2013)
There is great concern in Uganda about delays and cost overruns in public sector construction projects because such projects are implemented using taxpayers' money. At the national and international levels, there is considerable debate regarding how to minimise project delays and cost overruns. The main objective of this study was to investigate the causes of construction project delays and cost overruns in Uganda's public sector. Specifically, this study was conducted to identify the causes of delays and overruns and to rank them according to their frequency, severity and importance. The Civil Aviation Authority (CAA) was selected as a case study as a means of validating the results of the survey. Frequency index, severity index and importance index values were computed and all 20 factors involved were ranked. The five most important causes of delays in construction projects were found to be the following: changes to the scope of work, delayed payments, poor monitoring and control, the high cost of capital and political insecurity and instability. The relationship between the factors that cause delays and those that cause cost overruns was found to be moderate. Recommendations are made for improved project management, a change from the traditional contract type to the design–build type and improved cash flow on the part of the client to reduce payment delays. The results of this research should help construction practitioners, policy makers and researchers in the field of construction management.